Analisis Financial Distress dan Free Cash Flow dengan Proporsi Dewan Komisaris Independen sebagai Variabel Moderasi Terhadap Manajemen Laba - Bella Nabilla Lukita Putri; Sistya Rachmawati (STIE Indonesia Banking School, 2018)
This study investigates the effect of Financial Distress and Free Cash Flow on Earnings Management with the Board of Commissioners Independent as a moderating variable. This investigation usage the population of manufacturing companies positioned on the Indonesia stock exchange years 2014 to 2017 with a meager 152 companies, according to the criteria needed in this study there were only 53 manufacturing companies that became the sample for the year 2014 to 2017. The research of usage multiple regression analysis with the roles of research that the Financial Distress of positive appearance significantly to earnings Management, then to Free Cash Flow does not have an effect on Earnings Management. For variable Independent Commissioners only moderation that strengthens Free Cash Flow against the management, while for the Financial Distress does not strengthen his relationship with management